Effect of TaC/Ti/Si3N4 Hard Ceramics on Mechanical and Microstructural Behaviour of AA7075 Processed through Stir Casting Process. (22nd April 2022) - Pradeep Kumar, J.; Robinson Smart, D. S.; Manova, Stephen; Ummal Salmaan, N.
Abstract : A liquid metallurgical stir casting route was utilized for developing aluminium alloy (7075) matrix composites blended with fluctuating wt% of silicon nitride (Si3 N4 ), tantalum carbide (TaC), and titanium (Ti) for sake of generating a profitable composite with enhanced properties. The physical, microstructural, and mechanical characteristics such as density, high temperature tensile, fatigue, and time-dependent creep experiments were conducted and evaluated. SEM microstructural examinations were performed on the composite samples and proved that there was a good interfacial bonding and uniform dissemination among the reinforcement particulates in the matrix. Physical characteristics were analysed and the outcomes showed that AA7075 blended with 1 wt% TaC, 8 wt% Si3 N4, and 0.5 wt% Ti proved higher experimental and theoretical densities of 3.2464 g/cm 3 and 3.3038 g/cm 3, respectively, with maximum porosity of 1.7758%. At 30°C, the tensile properties of the developed MMCs showed improved ultimate tensile strength (UTS) of 137.64 N/mm 2 . Beyond 100°C, AA7075 reinforced with 0.75 wt% TaC, 6 wt% Si3 N4, and 1 wt% Ti proved to have a higher strength of 232.17 N/mm 2 . Fatigue properties of the developed MMCs discovered were found to be reformed when proportionate to the base alloy by operating at 14 × 10 3 cycles at the stress of 42.72 MPa. Time-dependent creep analysis of the developed MMCs found to be advanced due to the addition of tough ceramic particulates.